Model Pertanggungjawaban BUMDes Puji Berkah pada Unit Simpan Pinjam - Fatchur Rohman; Miftah Arifin (University of Merdeka Malang, 2020)
This paper describes the results of community service activities (PKM) at the Village-Owned Enterprises in Jepara that face accountability issues. The purpose of this community service program is to implement the BUMDes accountability model and BUMDes business management. The program implementation phase includes systematic development of the BUMDes accountability report, application and process of preparing BUMDes accountability report, development of a Simple Financial Information System, and assistance and application of a simple financial information system. The results of the community service program outputs are generated in the form of guidelines for preparing the accountability report of BUMDes Puji Berkah Sinanggul and simple saving and loan financial applications. Based on the results of the dedication, it can be formulated that the implementation of the accountability model of BUMDes Puji Berkah can improve the quality of the performance of existing managers of BUMDes which are the object of service. BUMDes fits the format and meets the timeliness of reporting. How to cite:Rohman, F., Arifin, M. (2020). Model Pertanggungjawaban BUMDes Puji Berkah pada Unit Simpan Pinjam. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 5(1), 18-27.DOI: https://doi.org/10.26905/abdimas.v5i1.3368